Wind force of super high-rise buildings with hexagonal section. (October 2021) - Wang, Lei; Zhang, Wei; Liu, li-sheng; Zhang, Zheng-hua
Abstract: To study the wind force of super high-rise buildings with hexagonal section, a series of wind tunnel tests of synchronous pressure models were carried out. The alongwind force coefficient, as well as the power spectral density (PSD) and the RMS base moment of crosswind force were studied. Thereafter, the empirical formulae of wind force were established. Meanwhile, wind tunnel tests of multiple-degree-of-freedom (MDOF) aero-models were conducted to measure the crosswind responses. The aerodynamic damping ratios were identified by analyzing the time histories of measured responses. Finally, the aerodynamic damping ratios obtained from the aero-model test and the analytical model of wind force obtained from the synchronous pressure model were combined to calculate the crosswind dynamic response. The comparison between the wind induced response of calculation result and that of aero-model test shows that the wind force analytical model proposed in this paper is reliable. This study can provide references for the wind resistance design and standard improvement of super high-rise buildings with hexagonal section.